2014
DOI: 10.1007/s13311-013-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cognitive, Psychiatric, and Affective Disorders Associated with Parkinson's Disease

Abstract: Neuropsychiatric symptoms are common in Parkinson's disease (PD) and add significantly to the burden of disease. These symptoms are most commonly part of the disease spectrum owing to pathological changes within relevant brain regions. Neuropsychiatric problems include disorders of cognition, ranging from mild cognitive impairment to dementia, psychotic symptoms, including, most commonly, well-formed visual hallucinations and paranoid delusions, and mood disorders, such as depression and anxiety. The other com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 171 publications
(184 reference statements)
1
48
0
4
Order By: Relevance
“…However, this mild dopaminergic damage triggered mood-related behavioral alterations, such as anhedonia, defense behaviors, and impaired social interaction, as also observed in previous studies [24][25][26]; thus, this 6-OHDA-based model is an experimental model well-suited to evaluate behaviors related to symptoms occurring in the PD prodrome [3,27,28], without affecting motor functions that could confound the interpretation of emotional parameters associated to defense behaviors relevant to depression and anhedonia. Furthermore, we now confirmed that fluoxetine and the atypical antidepressant drug bupropion prevented the appearance of these behavioral alterations, further validating the pertinence of these alterations to the PD-related depressive status [29,30]. This is particularly relevant since PD patients exhibit a wide range of non-motor symptoms such as anhedonia, depression, and anxiety that affect their quality of life and represent a major unmet therapeutic need [2,3,6].…”
Section: Discussionsupporting
confidence: 68%
“…However, this mild dopaminergic damage triggered mood-related behavioral alterations, such as anhedonia, defense behaviors, and impaired social interaction, as also observed in previous studies [24][25][26]; thus, this 6-OHDA-based model is an experimental model well-suited to evaluate behaviors related to symptoms occurring in the PD prodrome [3,27,28], without affecting motor functions that could confound the interpretation of emotional parameters associated to defense behaviors relevant to depression and anhedonia. Furthermore, we now confirmed that fluoxetine and the atypical antidepressant drug bupropion prevented the appearance of these behavioral alterations, further validating the pertinence of these alterations to the PD-related depressive status [29,30]. This is particularly relevant since PD patients exhibit a wide range of non-motor symptoms such as anhedonia, depression, and anxiety that affect their quality of life and represent a major unmet therapeutic need [2,3,6].…”
Section: Discussionsupporting
confidence: 68%
“…The approach of psychosis in PD is similar to that of a patient in delirium [32]. The first step is to identify any possible trigger(s).…”
Section: Current Expert Approachmentioning
confidence: 99%
“…Depression is a very common in dementia as part of PD. Therefore, its early identification is of the essence in order to begin early medicament therapy, which will in the long-run improve the quality of life both of the patient and the caregiver (11,16,21).…”
Section: Introductionmentioning
confidence: 99%